Steroid cell tumour-a rare ovarian tumour: a case report - Balathil, Ranjana; Pulpra, Ajitha; Vethavayal, Rabiyabi; Praveen, Ani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Steroid cell tumours of the ovary are sex cord stromal tumours which are rare, of all ovarian tumours. Case: Here we present a case of 35-year-old lady who presented to us with complaints of amenorrhoea. With thorough history taking, diagnostic workup and postoperative histopathological evaluation found to have a rare kind of ovarian tumor steroid cell tumor.